A study on clinical profile of stroke in young and elderly in GMERS Medical College and Hospital, Gandhinagar, Gujarat - Vaidya, Chirayu V.; Majmudar, Drusty K. (International Journal of Research in Medical Sciences, 2017)
Background:The cerebrovascular stroke is one of the leading causes of morbidity & mortality in adult life. Indian studies have shown a stroke prevalence of 471.58/100000 population. Stroke mostly occurs in elderly people. Risk factors for stroke differ between young and elderly patients. The aim was to study the clinical presentation, risk factors, types, topography as per CT scan findings in ≤45 years and >45 years patients from GMERS medical college and hospital Gandhinagar. Methods:This is a retrospective study of all new patients managed for stroke in the medical ward of GMERS medical college and hospital, Gandhinagar, Gujarat from January1, 2012 to December 31, 2013. Results:Incidence of stroke in elderly (≥45 years) was than young (<45 years) patients with male predominance in both the groups. Most common clinical presentation from both age groups was hemiplegia (75% in young vs. 72.1% in elderly). Common risk factors in were HT and past h/o CVD (25%) and smoking (16.6%) in young and HT (37.1%), dyslipidemia and smoking (14.3%) in elderly. Most common type of stroke in both age groups was ischemic (83.3% in young vs. 73.2% in elderly), followed by Hemorrhagic. Common sites of hemorrhage in young and elderly were lobar and thalamoganglionic. Most common infarction site in both age groups is MCA territory. Conclusion:The cerebrovascular stroke was more in elderly with hypertension and smoking was the most common risk factor in both age groups and most common type was ischemic.